Early Catastrophic Failure of a PINNACLE MARATHON® Polyethylene Acetabular Liner: A Report of a Malpositioned PINNACLE DUOFIX HA® Acetabular Shell Resulting in Point Loading and Accelerated Wear. Issue 6 (10th November 2016) - Hill, Daniel S.; Patel, Kuntal; Herlekar, Deepak
Background: Highly cross-linked polyethylene in total hip arthroplasty (THA) has been shown to decrease wear rate compared with a conventional polyethylene liner. However, it has also been reported that the manufacturing processes can cause early failure of the implant. Case: We describe early catastrophic failure at <4 years following primary THA surgery of a PINNACLE MARATHON® polyethylene acetabular liner resulting from a malaligned PINNACLE DUOFIX HA® acetabular shell with resultant point loading. Radiographs revealed a malaligned acetabular shell and superior subluxation of the femoral head out of the liner. At revision surgery operative findings revealed that the acetabular shell alignment was in of 50° of anteversion and 70° of inclination. Significant metallosis in the surrounding tissues was observed. Conclusions: We conclude that a malpositioned acetabular shell resulting in point loading and abnormal contact stresses was the mechanism of failure. Our case highlights the importance of achieving correct acetabular component alignment in total hip arthroplasty.